High-specific-capacity low-temperature aqueous sulfur-based battery and preparation method thereof

By using high specific capacity sulfur-based battery modules and optimized electrolytes in low-temperature water-based batteries, the problem of difficulty in operating and low capacity in extremely low-temperature environments is solved, and the effect of providing stable energy supply in high-altitude environments is achieved.

CN119890482AActive Publication Date: 2025-04-25SICHUAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510081061.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-25
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The existing low-temperature water system batteries are difficult to operate normally in extremely low-temperature environments, and their capacity is low, which limits their application in high-altitude environments.

Method used

A low-temperature water-based sulfur-based battery with high specific capacity is adopted, which includes a positive electrode, an anode, an electrolyte and an ion exchange membrane. The positive electrode is composed of a sulfur-carbon composite, a conductive agent and a binder. The electrolyte is made of copper or zinc salt electrolytes to improve the performance of the battery by optimizing the mass ratio of the components and the preparation method.

Benefits of technology

In an environment of -50℃, the battery can supply energy stably, provide ultra-high specific capacity and good cycle stability, and meet the application needs of high-altitude environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890482A_ABST
    Figure CN119890482A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and provides a high-specific-capacity low-temperature aqueous sulfur-based battery and a preparation method thereof. The high-specific-capacity low-temperature aqueous sulfur-based battery comprises a positive electrode, a negative electrode, an electrolyte and an ion exchange membrane, the positive electrode comprises a positive electrode current collector and a positive electrode diaphragm; the positive electrode membrane comprises a sulfur-carbon compound, a conductive agent and a binder. The battery can stably supply energy in extremely low-temperature environments such as high altitude, deep space and deep sea, has ultrahigh specific capacity and excellent electrochemical performance, also has the characteristics of low cost, high safety and simple preparation process, greatly improves the application potential of the low-temperature water-based sulfur-based battery in various high severe cold environments, and has wide application prospects. And the development of the energy storage industry is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a high specific capacity, low temperature aqueous sulfur-based battery and a preparation method thereof. Background Art

[0002] Large-scale energy storage systems have shown great potential in the process of integrating renewable energy such as wind and solar energy, and for this reason, they have received more and more attention. Among the many types of energy storage systems, rechargeable aqueous batteries stand out with their advantages of low cost, good safety and environmentally friendly benefits, and have become a highly anticipated existence. However, it is regrettable that water itself has a high freezing point, which makes aqueous batteries very easy to freeze in low temperature environments. Once frozen, its kinetic performance will be reduced, and the interfacial reaction between the electrolyte and the electrode will be aggravated, which will eventually make it difficult for the aqueous battery to operate normally and fail to play its due role. At present, the design of low-temperature aqueous electrolytes adopts a variety of strategies, such as using high-concentration electrolytes, adding organic additives, and using antifreeze hydrogel electrolytes. However, these strategies also bring many obstacles in practical application. Specifically, if a high-concentration electrolyte is used, it will not only increase the cost, but also cause a decrease in ionic conductivity; and the added organic substances often have harmful or toxic properties, which undoubtedly bury certain safety risks; as for hydrogel electrolytes, their preparation process is relatively complicated and requires additional preparation steps.

[0003] In addition, as far as the existing low-temperature aqueous batteries are concerned, they mostly use the reaction mechanism of ion insertion and extraction, and the common materials are vanadium-based oxides or manganese-based oxides. However, the capacity that these batteries can provide is generally at a relatively low level, which greatly limits the effective application of low-temperature aqueous batteries in high-cold environments, making it difficult for them to fully play their role and meet actual needs.

[0004] Therefore, it is of great significance to develop a high-specific-capacity, low-temperature aqueous sulfur-based battery that can stably provide energy in extreme low-temperature environments such as high altitudes, deep space, and deep sea. Summary of the invention

[0005] In view of this, the present invention provides a high specific capacity low-temperature aqueous sulfur-based battery and a preparation method thereof to solve the problem that the existing aqueous batteries have low capacity and are difficult to operate normally in extreme low temperature environments.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The present invention provides a high specific capacity, low temperature aqueous sulfur-based battery, which comprises a positive electrode, a negative electrode, an electrolyte and an ion exchange membrane; the positive electrode comprises a positive electrode collector and a positive electrode membrane; the positive electrode membrane comprises a sulfur-carbon composite, a conductive agent and a binder.

[0008] Preferably, the sulfur-carbon composite is formed by sintering sulfur powder and carbon powder; the mass ratio of the sulfur powder to the carbon powder is 0.5-3:1; the carbon powder includes one or more of carbon nanotubes, carbon black, porous carbon and graphite; the sintering temperature is 80-200°C and the time is 6-18h.

[0009] Preferably, the mass ratio of the sulfur-carbon composite, the conductive agent and the binder is 4-12:0.2-2:0.2-2.

[0010] Preferably, the conductive agent includes one or more of carbon black, acetylene black and graphite; the binder includes one or both of polyvinylidene fluoride and polytetrafluoroethylene; and the positive electrode current collector includes one or more of titanium foil, stainless steel mesh and carbon cloth.

[0011] Preferably, the method for preparing the positive electrode comprises the following steps: mixing the sulfur-carbon composite, the conductive agent and the binder, applying the mixture on the positive electrode current collector, and drying the mixture to obtain the positive electrode.

[0012] Preferably, the area load of the coating is 0.1 to 5 mg / cm 2 ; The drying temperature is 50-70°C and the time is 10-14h.

[0013] Preferably, the negative electrode is a zinc negative electrode or a copper negative electrode; when the negative electrode is a copper negative electrode, the electrolyte comprises a copper salt electrolyte and water, and the molar concentration of the copper salt electrolyte is 0.5 to 6 mol / L.

[0014] Preferably, when the negative electrode is a zinc negative electrode, the electrolyte comprises a positive electrode electrolyte and a negative electrode electrolyte, the positive electrode electrolyte comprises a copper salt electrolyte and water, and the negative electrode electrolyte comprises a zinc salt electrolyte and water.

[0015] Preferably, the molar concentrations of the positive electrode electrolyte and the negative electrode electrolyte are independently 3 to 5 mol / L.

[0016] Preferably, the copper salt electrolyte is Cu(BF 4 ) 2 ; The zinc salt electrolyte is Zn(BF 4 ) 2 .

[0017] The present invention also provides a method for preparing a high specific capacity, low temperature aqueous sulfur-based battery. When the negative electrode is a copper negative electrode, the method for preparing the high specific capacity, low temperature aqueous sulfur-based battery comprises the following steps: assembling the positive electrode, ion exchange membrane, electrolyte and copper negative electrode, and packaging them on a button battery packaging machine to obtain a high specific capacity, low temperature aqueous sulfur-based battery.

[0018] Preferably, when the negative electrode is a zinc negative electrode, the preparation method of the high specific capacity low temperature aqueous sulfur-based battery comprises the following steps: assembling the positive electrode, positive electrode electrolyte, ion exchange membrane, negative electrode electrolyte and zinc negative electrode, placing them on a button battery packaging machine for packaging, and obtaining a high specific capacity low temperature aqueous sulfur-based battery.

[0019] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0020] The high specific capacity low temperature aqueous sulfur-based battery of the present invention has the characteristics of ultra-high specific capacity and stable energy supply in extreme low temperature environments such as high altitude, deep space and deep sea. Among them, when the negative electrode is a copper negative electrode, the prepared Cu-S half-cell can operate stably at an ultra-low temperature of -50°C and has a capacity of 2996mAh·g at -50°C. -1 Ultra-high initial capacity and 1612mAh g -1 When the negative electrode is zinc, the prepared Zn-S full battery can also operate stably at an ultra-low temperature of -50°C, with a reversible capacity of more than 1700 mAh g at -50°C. -1 In summary, the high specific capacity low-temperature aqueous sulfur-based battery of the present invention can provide stable energy supply in an environment of -50°C, and can effectively apply the low-temperature aqueous sulfur-based battery in a high-cold environment, so that it can fully play its role and meet actual needs. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0022] Figure 1 The molar concentration of Cu(BF) is 3.5 mol / L 4 ) 2 Optical image of aqueous electrolyte at -60℃ for 30min;

[0023] Figure 2 The first three charge-discharge curves of the low-temperature aqueous Cu-S battery prepared in Example 1 at -50°C;

[0024] Figure 3 This is a rate performance curve of the low-temperature aqueous Cu-S battery prepared in Example 1 at -50°C;

[0025] Figure 4 The first three charge-discharge curves of the low-temperature aqueous Cu-S battery prepared in Example 2 at -50°C;

[0026] Figure 5 The first three charge-discharge curves of the low-temperature aqueous Cu-S battery prepared in Example 3 at -50°C;

[0027] Figure 6 This is a physical picture of the low-temperature aqueous Zn-S battery prepared in Example 4;

[0028] Figure 7 The molar concentration of Zn(BF 4 ) 2 Optical image of aqueous electrolyte at -60℃ for 30min

[0029] Figure 8 The first three charge and discharge curves of the low-temperature aqueous Zn-S battery prepared in Example 4 at room temperature;

[0030] Fig. 9 This is a rate performance diagram of the low-temperature aqueous Zn-S battery prepared in Example 4 at room temperature;

[0031] Fig.10 The first three charge-discharge curves of the low-temperature aqueous Zn-S battery prepared in Example 4 at -50°C;

[0032] Fig.11 This is a cycle performance diagram of the low-temperature aqueous Zn-S battery prepared in Example 4 at -50°C;

[0033] Fig.12 This is the rate performance diagram of the low-temperature aqueous Zn-S battery prepared in Example 5 at -50°C. DETAILED DESCRIPTION

[0034] The present invention provides a high specific capacity, low temperature aqueous sulfur-based battery, which comprises a positive electrode, a negative electrode, an electrolyte and an ion exchange membrane; the positive electrode comprises a positive electrode collector and a positive electrode membrane; the positive electrode membrane comprises a sulfur-carbon composite, a conductive agent and a binder.

[0035] In the present invention, the sulfur-carbon composite is formed by sintering sulfur powder and carbon powder; the sintering is preferably performed by first mixing the sulfur powder and the carbon powder and grinding them, and then placing them in a tube furnace for sintering; the grinding time is preferably 15 to 25 minutes, more preferably 18 to 22 minutes, and more preferably 20 minutes.

[0036] In the present invention, the mass ratio of the sulfur powder to the carbon powder is 0.5 to 3:1, preferably 0.7 to 2.8:1, more preferably 1.0 to 2.5:1, and more preferably 1.5 to 2.0:1; the carbon powder includes one or more of carbon nanotubes, carbon black, porous carbon and graphite, preferably includes one or more of carbon nanotubes, porous carbon and graphite, and more preferably carbon nanotubes; the firing temperature is 80 to 200°C, preferably 90 to 180°C, more preferably 100 to 160°C, and more preferably 120 to 130°C; the firing time is 6 to 18h, preferably 8 to 16h, more preferably 10 to 14h, and more preferably 12h.

[0037] In the present invention, the mass ratio of the sulfur-carbon composite, the conductive agent and the binder is 4-12:0.2-2:0.2-2, preferably 5-10:0.5-1.5:0.5-1.5, and more preferably 8:1:1.

[0038] In the present invention, the conductive agent includes one or more of carbon black, acetylene black and graphite; the binder includes one or two of polyvinylidene fluoride and polytetrafluoroethylene; the positive electrode current collector includes one or more of titanium foil, stainless steel mesh and carbon cloth, preferably stainless steel mesh.

[0039] In the present invention, the preparation method of the positive electrode comprises the following steps: mixing the sulfur-carbon composite, the conductive agent and the binder, applying the mixture on the positive electrode current collector, and drying the mixture to obtain the positive electrode.

[0040] In the present invention, the area load of the coating is 0.1 to 5 mg / cm 2 , preferably 0.5 to 4 mg / cm 2 , more preferably 1 to 3 mg / cm 2 , more preferably 1.5 to 2.5 mg / cm 2 The drying temperature is 50 to 70°C, preferably 52 to 68°C, more preferably 55 to 65°C, and more preferably 60°C; the drying time is 10 to 14h, preferably 10.5 to 13.5h, more preferably 11 to 13h, and more preferably 12h.

[0041] In the present invention, the negative electrode is a zinc negative electrode or a copper negative electrode; when the negative electrode is a copper negative electrode, the electrolyte comprises a copper salt electrolyte and water, and the molar concentration of the copper salt electrolyte is 0.5 to 6 mol / L, preferably 1.0 to 5.5 mol / L, further preferably 1.5 to 5.0 mol / L, and more preferably 2.0 to 3.0 mol / L.

[0042] In the present invention, when the negative electrode is a zinc negative electrode, the electrolyte includes a positive electrode electrolyte and a negative electrode electrolyte, the positive electrode electrolyte includes a copper salt electrolyte and water, and the negative electrode electrolyte includes a zinc salt electrolyte and water.

[0043] In the present invention, the molar concentrations of the positive electrode electrolyte and the negative electrode electrolyte are independently 3 to 5 mol / L, preferably 3.2 to 4.8 mol / L, more preferably 3.5 to 4.5 mol / L, and even more preferably 4.0 mol / L.

[0044] In the present invention, the copper salt electrolyte is Cu(BF 4 ) 2 ; The zinc salt electrolyte is Zn(BF 4 ) 2 .

[0045] In the present invention, the Cu(BF 4 ) 2 The F element in the copper salt electrolyte has a higher electronegativity and is a potential HB acceptor, making it easier to form hydrogen bonds with water molecules. 4 - With four BF bonds, it can form various HBs with water molecules, greatly destroying the hydrogen bond network of the original water environment and reducing the formation of water clusters. This can make Cu(BF 4 ) 2 The electrolyte formed by copper salt electrolyte and water has a lower freezing point, which improves the conductivity of the electrolyte at low temperature. At the same time, sulfur has a large abundance and a high theoretical specific capacity, and can react with Cu in aqueous solution. 2+ Combined to form Cu 2 S, this reaction has four electron transfer and has 3350mAh·g -1 The theoretical specific capacity greatly improves the performance of low-temperature aqueous sulfur-based batteries.

[0046] The present invention also provides a method for preparing a high specific capacity, low temperature aqueous sulfur-based battery. When the negative electrode is a copper negative electrode, the method for preparing the high specific capacity, low temperature aqueous sulfur-based battery comprises the following steps: assembling the positive electrode, ion exchange membrane, electrolyte and copper negative electrode, and packaging them on a button battery packaging machine to obtain a high specific capacity, low temperature aqueous sulfur-based battery.

[0047] In the present invention, when the negative electrode is a zinc negative electrode, the preparation method of the high specific capacity low temperature aqueous sulfur-based battery includes the following steps: assembling the positive electrode, positive electrode electrolyte, ion exchange membrane, negative electrode electrolyte and zinc negative electrode, placing them on a button battery packaging machine for packaging, and obtaining a high specific capacity low temperature aqueous sulfur-based battery.

[0048] In the present invention, when the negative electrode is a zinc negative electrode, a Zn is used in the negative electrode electrolyte by a decoupling carrier strategy. 2+ Electrolyte, Cu is used in the positive electrode electrolyte 2+ The electrolyte is separated from the positive electrode by an ion exchange membrane, allowing only anions to pass through.

[0049] In the present invention, the Zn negative electrode has a lower redox potential (-0.76V vs. SHE), and the Zn-S battery assembled with S has an operating voltage of 1.2V, which greatly improves the energy density of the low-temperature aqueous Zn-S battery.

[0050] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0051] Example 1 Preparation of low temperature aqueous Cu-S battery

[0052] First, a sulfur-carbon composite was prepared: sulfur powder and carbon nanotube powder in a mass ratio of 2:1 were placed in an agate mortar, alcohol was added and ground and mixed for 20 minutes to obtain a sulfur-carbon mixture, and then the sulfur-carbon mixture was placed in a tubular furnace and sintered at 155°C for 12 hours to obtain a sulfur-carbon composite.

[0053] Secondly, prepare the positive electrode: the sulfur-carbon composite obtained above, conductive carbon black and polyvinylidene fluoride are placed in an agate mortar in a mass ratio of 8:1:1, and N-methylpyrrolidone (NMP) solvent (the mass volume ratio of binder polyvinylidene fluoride and NMP is 32 mg:1 mL) is added for grinding. After grinding for 20 minutes, the positive electrode slurry is obtained; the positive electrode slurry is evenly applied on the stainless steel mesh current collector, and the area load of the coating is 2 mg / cm 2 , and then place the coated stainless steel mesh in a vacuum environment at 60°C and dry it for 12 hours to obtain the positive electrode.

[0054] Finally, prepare the low-temperature aqueous Cu-S battery: take the battery positive electrode shell, use tweezers to pick up the prepared battery positive electrode and place it in the center of the positive electrode shell, cover it with an ion exchange membrane, and then use a rubber-tipped dropper to absorb 150 μL of Cu(BF) with a molar concentration of 3.5 mol / L. 4 ) 2The electrolyte is dropped onto the ion exchange membrane to fully soak the membrane, and then the copper sheet negative electrode is placed on the soaked ion exchange membrane. The active part of the battery is then covered with a gasket, and a spring sheet is placed on the gasket. The negative electrode cover is closed, and after assembly, it is placed on a button cell packaging machine for packaging to obtain a low-temperature aqueous Cu-S battery.

[0055] The molar concentration of Cu(BF) in this example is 3.5 mol / L. 4 ) 2 The electrolyte was placed in a -60℃ low temperature box for 30 minutes for antifreeze test. The test results are as follows: Figure 1 As shown, from Figure 1 It can be seen that the Cu(BF 4 ) 2 After the electrolyte was kept at -60°C for 30 minutes, it still remained in a transparent liquid state, proving that the Cu(BF 4 ) 2 The electrolyte has excellent antifreeze ability.

[0056] The low-temperature aqueous Cu-S battery prepared in this example was placed in the Xinwei battery test system and its charge and discharge performance was tested at a temperature of -50°C. Figure 2 As shown, from Figure 2 It can be seen that the low-temperature aqueous Cu-S battery prepared in this example has a -1 At the current of , the first cycle has 2996mAh·g -1 The second and third circles almost overlap, which means that the battery has an initial capacity of 1612 mAh g -1 High reversible capacity.

[0057] The low-temperature aqueous Cu-S battery prepared in this example was tested for rate performance at -50°C. The results are as follows: Figure 3 As shown, from Figure 3 It can be seen that the low-temperature aqueous Cu-S battery prepared in this example has a -1 The high current still maintains 1132mAh·g -1 This shows that the battery has excellent rate performance.

[0058] Example 2 Preparation of low temperature aqueous Cu-S battery

[0059] The difference between this embodiment and embodiment 1 is that the electrolyte is Cu(BF) with a molar concentration of 4 mol / L. 4 ) 2 Solution.

[0060] The low-temperature aqueous Cu-S battery prepared in this example was tested for rate performance at -50°C. The results are as follows: Figure 4 As shown, from Figure 4 It can be seen that the low-temperature aqueous Cu-S battery prepared in this example has good cycle stability and low-temperature working performance. At a temperature of -50°C, it can release 3200mAh·g -1 The second circle and the third circle almost overlap, which means that the battery has a capacity of 1800mAh g -1 High reversible capacity.

[0061] Example 3 Preparation of low temperature aqueous Cu-S battery

[0062] The difference between this embodiment and embodiment 1 is that the electrolyte is Cu(BF) with a molar concentration of 5 mol / L. 4 ) 2 Solution.

[0063] The low-temperature aqueous Cu-S battery prepared in this example was tested for rate performance at -50°C. The results are as follows: Figure 5 As shown, from Figure 5 It can be seen that the low-temperature aqueous Cu-S battery prepared in this example has good cycle stability and low-temperature working performance. At a temperature of -50°C, it can release 3100mAh·g -1 The second circle and the third circle almost overlap, which means that the battery has a capacity of 1750mAh g -1 High reversible capacity.

[0064] Example 4 Preparation of Low-Temperature Aqueous Zn-S Battery

[0065] The preparation method of the sulfur-carbon composite and the positive electrode in this Example 4 is the same as that in Example 1.

[0066] Preparation of low-temperature aqueous Zn-S battery: Place the positive electrode on a glass plate, and then assemble in the order of positive electrode electrolyte, ion exchange membrane, negative electrode electrolyte, and zinc negative electrode; after assembly, place it on a button battery packaging machine for packaging to obtain a low-temperature aqueous Zn-S battery. Among them, the ion exchange membrane separates the positive electrode electrolyte and the negative electrode electrolyte, allowing anions to shuttle between them; the positive electrode electrolyte is Cu(BF) with a molar concentration of 3.5 mol / L 4 ) 2 The negative electrode electrolyte is Zn(BF 4 ) 2 Electrolyte.

[0067] The actual picture of the low-temperature aqueous Zn-S battery prepared in this example is as follows Figure 6 shown.

[0068] The molar concentration of Cu(BF) in this example is 3.5 mol / L. 4 ) 2 The electrolyte and Zn(BF 4 ) 2 The electrolyte was placed in a -60℃ low temperature box for antifreeze test. The test results are as follows: Figure 1 and Figure 7 As shown, from Figure 1 and Figure 7 It can be seen from the figure that after being kept in a low temperature box at -60°C for 30 minutes, the Cu(BF 4 ) 2 Electrolyte and Zn(BF 4 ) 2 The electrolytes are all in a transparent liquid state, proving that the Cu(BF 4 ) 2 and Zn(BF 4 ) 2 The electrolyte has excellent antifreeze ability.

[0069] After testing, the charge and discharge performance and rate performance of the low-temperature aqueous Zn-S battery prepared in this embodiment at room temperature are as follows: Figures 8-9 As shown. Among them, from Figure 8 As can be seen from the charge and discharge performance results, the first cycle capacity of the low-temperature aqueous Zn-S battery prepared in this embodiment can reach 2924 mAh g in the first three cycles of charge and discharge curves at room temperature. -1 , with a capacity of up to 1741mAh·g -1 The reversible capacity of Fig. 9 As can be seen from the rate performance results, even at 2A·g -1 Under high current, the low-temperature aqueous Zn-S battery prepared in this embodiment can still retain 1287 mAh·g -1 This shows that the battery has excellent rate performance.

[0070] The charge-discharge performance and rate performance of the low-temperature aqueous Zn-S battery prepared in this example at -50°C are shown in the figure. Figures 10-11 As shown. Among them, from Fig.10 As can be seen from the charge and discharge performance results, the low-temperature aqueous Zn-S battery prepared in this embodiment does not show any attenuation in battery capacity at an ultra-low temperature of -50°C. The first cycle release capacity at -50°C is 3000mAh·g -1 The charge and discharge curves of the second and third cycles are almost overlapped, indicating that the battery has a capacity of more than 1700mAh·g -1 The reversible capacity of Fig.11It can be seen from the rate performance result diagram that the low-temperature aqueous Zn-S battery prepared in this embodiment can be stably cycled for more than 200 cycles at -50°C, indicating that the battery has excellent cycle stability.

[0071] In summary, the low-temperature aqueous Zn-S battery prepared in this example has excellent electrochemical performance, which achieves more than 1700 mAh·g at -50 °C. -1 The ultra-high discharge specific capacity can provide stable energy supply in an environment of minus 50 degrees Celsius. In addition, the battery also has faster reaction kinetics and lower polarization. This greatly improves the application potential of low-temperature aqueous sulfur-based batteries in various severe cold environments, enabling them to be more widely used in extreme low temperature conditions.

[0072] Example 5 Preparation of Low-Temperature Aqueous Zn-S Battery

[0073] The difference between this embodiment and embodiment 4 is that the positive electrode electrolyte is Cu(BF) with a molar concentration of 4 mol / L. 4 ) 2 The negative electrode electrolyte is Zn(BF 4 ) 2 Electrolyte.

[0074] After testing, the rate performance results of the low-temperature aqueous Zn-S battery prepared in this embodiment at -50°C are as follows: Fig.12 As shown. Fig.12 It can be seen that the low-temperature aqueous Zn-S battery prepared in this embodiment has good cycle stability and low-temperature working performance. -1 Under high current, the low-temperature aqueous Zn-S battery prepared in this embodiment can still retain 979 mAh·g -1 The battery has a high capacity and good reversibility, which indicates that the battery has excellent rate performance and cycle performance.

[0075] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high specific capacity low temperature aqueous sulfur-based battery, characterized in that: The high specific capacity low temperature aqueous sulfur-based battery comprises a positive electrode, a negative electrode, an electrolyte and an ion exchange membrane; The positive electrode comprises a positive electrode current collector and a positive electrode membrane; The positive electrode membrane comprises a sulfur-carbon composite, a conductive agent and a binder.

2. A high specific capacity low temperature aqueous sulfur-based battery according to claim 1, characterized in that: The sulfur-carbon composite is formed by sintering sulfur powder and carbon powder; The mass ratio of the sulfur powder to the carbon powder is 0.5 to 3:1; The carbon powder includes one or more of carbon nanotubes, carbon black, porous carbon and graphite; The firing temperature is 80-200° C. and the firing time is 6-18 hours.

3. A high specific capacity low temperature aqueous sulfur-based battery according to claim 2, characterized in that: The mass ratio of the sulfur-carbon composite, the conductive agent and the binder is 4-12:0.2-2:0.2-2.

4. A high specific capacity low temperature aqueous sulfur-based battery according to any one of claims 1 to 3, characterized in that: The conductive agent includes one or more of carbon black, acetylene black and graphite; The binder includes one or both of polyvinylidene fluoride and polytetrafluoroethylene; The positive electrode current collector includes one or more of titanium foil, stainless steel mesh and carbon cloth.

5. A high specific capacity low temperature aqueous sulfur-based battery according to claim 4, characterized in that: The preparation method of the positive electrode comprises the following steps: The sulfur-carbon composite, the conductive agent and the binder are mixed, applied on the positive electrode current collector, and dried to obtain the positive electrode.

6. A high specific capacity low temperature aqueous sulfur-based battery according to claim 5, characterized in that: The area load of the coating is 0.1 to 5 mg / cm 2 ; The drying temperature is 50-70° C. and the drying time is 10-14 hours.

7. A high specific capacity low temperature aqueous sulfur-based battery according to claim 6, characterized in that: The negative electrode is a zinc negative electrode or a copper negative electrode; When the negative electrode is a copper negative electrode, the electrolyte includes a copper salt electrolyte and water, and the molar concentration of the copper salt electrolyte is 0.5 to 6 mol / L; When the negative electrode is a zinc negative electrode, the electrolyte includes a positive electrode electrolyte and a negative electrode electrolyte, the positive electrode electrolyte includes a copper salt electrolyte and water, and the negative electrode electrolyte includes a zinc salt electrolyte and water; The molar concentrations of the positive electrode electrolyte and the negative electrode electrolyte are independently 3 to 5 mol / L.

8. A high specific capacity low temperature aqueous sulfur-based battery according to claim 7, characterized in that: The copper salt electrolyte is Cu(BF4)2; the zinc salt electrolyte is Zn(BF4)2.

9. A method for preparing a high specific capacity low temperature aqueous sulfur-based battery according to any one of claims 1 to 8, characterized in that: When the negative electrode is a copper negative electrode, the preparation method of the high specific capacity low temperature aqueous sulfur-based battery comprises the following steps: After assembling the positive electrode, ion exchange membrane, electrolyte and copper negative electrode, they are placed on a button cell packaging machine for packaging to obtain a high specific capacity, low temperature aqueous sulfur-based battery; When the negative electrode is a zinc negative electrode, the preparation method of the high specific capacity low temperature aqueous sulfur-based battery comprises the following steps: After assembling the positive electrode, positive electrode electrolyte, ion exchange membrane, negative electrode electrolyte and zinc negative electrode, they are placed on a button battery packaging machine for packaging to obtain a high specific capacity, low-temperature aqueous sulfur-based battery.

Citation Information

Patent Citations

  • Low-temperature copper metal battery electrolyte and copper metal battery

    CN115312881A

  • Bipolar electrolyte for aqueous zinc-sulfur battery

    CN116315153A

  • Rechargeable aqueous sulfur-manganese battery

    CN117497880A

  • Aqueous battery based on sulfur positive electrode

    CN118336148A